A new species of Hyalinobatrachium (Centrolenidae: Anura) from Serranía de Perijá, Venezuela - Castroviejo-Fisher, Santiago; Ayarzagüena, José; Vilà, Carles (Zootaxa, 2007)
We describe a new species of Hyalinobatrachium from Serranía de Perijá, Estado de Zulia, Venezuela. The new species is placed in the Hyalinobatrachium fleischmanni group and can be differentiated from all other species of Hyalinobatrachium by having small enamelled glands on the lower part of the upper lip and on the skin covering the jaw, iris with a horizontal dark band that connects the pupil with the lateral edges of the eye, marked ulnar and tarsal white enamelled folds, extensive webbing between fingers and between toes, white pericardium and an advertisement call formed by a high-pitched single note composed of two parts: a group of modulated pulses increasing in frequency followed by a long and modulated sound at a constant frequency.